Anti-aging additive for asphalt binders and roofing materials
Patent Information
- Application Number
- JP2023540763
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-01-20
- Filing Date
- 2022-01-20
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2042-01-20
AI Technical Summary
Asphalt materials deteriorate over time due to aging, losing flexibility and becoming brittle, which affects their performance in paving and roofing applications, making recycled materials difficult to process and integrate with virgin binders.
Incorporation of modified anti-aging agents with high hydroxyl numbers, derived from carbonyl-containing compounds, to react with asphalt binders, forming hydroxyl groups and improving compatibility and flexibility, thereby retarding the aging process.
The modified anti-aging agents enhance the processing and performance properties of asphalt binders, allowing for increased use of recycled materials and extending the service life of asphalt-based products.
Abstract
Description
[Background technology]
[0001] Asphalt materials (e.g., asphalt paving materials and asphalt shingles) are some of the most recycled materials in the world and find use when recycled in paved surfaces and bridge abutment shoulders, as a substitute for gravel in unpaved roads, and as a replacement for virgin asphalt binder in new recycled pavement mixes. Recycling asphalt poses certain challenges because asphalt deteriorates over time, loses flexibility, oxidizes, becomes brittle, and tends to crack, especially when under stress or at low temperatures. These effects are primarily due to the aging of the organic components of the asphalt binder, e.g., bitumen-containing binders, especially when exposed to weather. Aged asphalt binders are also highly viscous. As a result, recycled asphalt materials often have different properties than virgin asphalt binders and are difficult to process. In paving and roofing applications, the composition of the materials used to create either the path or the roof will determine to a great extent the performance (e.g., aging, cracking, bubbling, moisture resistance, abrasion resistance, algae resistance, flexibility / adjustability, and adhesion) of the resulting paving and roofing material. Summary of the Invention
[0002] Compositions and methods are disclosed that can delay, reduce, or otherwise overcome the effects of aging of virgin or aged asphalt materials that preserve or rejuvenate some or all of the original properties of the virgin asphalt binder originally used. In some embodiments, the disclosed compositions and methods can modify the aging rate and performance characteristics of the total asphalt binder present in an asphalt binder mix containing virgin asphalt and recycled asphalt binder materials, including asphalt paving material (RAP), asphalt shingles (RAS), or both.
[0003] The disclosed asphalt binder compositions or mixtures may be used in a number of applications, including, but not limited to, in the production of moisture barrier and waterproofing films, underlayments, asphalt-based adhesives and sealants, roofing materials (such as roofing shingles, rolled roofing materials, and built-up roofing), asphalt paving materials, asphalt paving restoration or protection materials, and the like. Typically, roofing materials include a substrate such as a fiberglass mat, an asphalt-based coating that saturates the substrate and coats the top and bottom, and a layer of granules embedded in the top coating. The asphalt coating may also contain a filler, such as crushed limestone. Roofing shingles may also have a backside coating that contains a backdust material, such as silica sand, to prevent the shingles from sticking together when bundled. Paving materials typically include a mixture of asphalt binder, aggregate particles, and other optional additives.
[0004] The disclosed compositions and methods use modified asphalt anti-aging agents that are modified to contain high levels of free hydroxyl groups. Such modified anti-aging agents can improve processing and performance characteristics in virgin, recycled, and especially oxidized asphalt binder materials. Furthermore, the incorporation of such anti-aging agents can slow the deleterious effects of aging of virgin asphalt binders, enable the use of greater amounts of recycled asphalt materials, or both.
[0005] In some embodiments, the present disclosure describes an asphalt binder composition for use in producing a moisture barrier or waterproofing film, an underlay, an asphalt-based adhesive or sealant, a roofing material, an asphalt paving material, or an asphalt pavement restoration or protection material. The asphalt binder composition may have an asphalt binder containing at least one of virgin asphalt binder, air-blown virgin asphalt binder, recycled asphalt binder material (RAP) including asphalt paving material, or recycled asphalt binder material (RAS) including asphalt shingles. The composition also has an anti-aging agent that is a reaction product of components including (i) a first material including a compound containing one or more carbonyl groups, and (ii) a second material that reacts with one or more carbonyl groups of the first material to add hydroxyl groups to the reaction product, where the anti-aging agent has a hydroxyl number of greater than about 25 mg KOH / g.
[0006] In another embodiment, the present disclosure describes an asphalt-containing material comprising an asphalt binder composition comprising an asphalt binder containing at least one of virgin asphalt binder, airblown virgin asphalt binder, recycled asphalt binder material with RAP, or recycled asphalt binder material with RAS. The asphalt binder composition also has an anti-aging agent that is a reaction product of components including (i) a first material comprising a compound containing one or more carbonyl groups, and (ii) a second material that reacts with one or more carbonyl groups of the first material to add hydroxyl groups to the reaction product, where the anti-aging agent comprises a hydroxyl number greater than about 25 mg KOH / g. Examples of asphalt-containing materials may include, but are not limited to, a moisture barrier or waterproofing film, an underlay, an asphalt-based adhesive or sealant, a roofing material, an asphalt paving material, or an asphalt pavement restoration or protection material.
[0007] In another embodiment, the disclosure describes a method for retarding the effects of aging of an asphalt-containing material comprising forming an asphalt binder composition by adding an anti-aging agent to an asphalt binder, where the asphalt binder comprises at least one of a virgin asphalt binder, an air-blown virgin asphalt binder, a recycled asphalt binder material comprising RAP, or a recycled asphalt binder material comprising RAS, and the anti-aging agent is a reaction product of components comprising: (i) a first material comprising a compound containing one or more carbonyl groups, and (ii) a second material that reacts with the one or more carbonyl groups of the first material to add hydroxyl groups to the reaction product, where the anti-aging agent comprises a hydroxyl number of greater than about 25 mg KOH / g.
[0008] In another embodiment, the disclosure describes a method of making an asphalt-containing material, such as a moisture barrier or waterproofing film, an underlayment, an asphalt-based adhesive or sealant, a roofing material, or an asphalt paving material, the method comprising adding an anti-aging agent as described herein to an asphalt binder composition to form a coating composition, the coating composition comprising virgin asphalt binder, oxidized (e.g., air-blown) asphalt binder, aged asphalt binder, such as RAP or RAS, or a combination thereof.
[0009] In another embodiment, the disclosure describes a roofing material comprising a coated roofing substrate, the coating or saturation comprising an asphalt binder composition containing an asphalt binder, and an anti-aging agent that is a reaction product of components including: (i) a first material comprising a compound containing one or more carbonyl groups, and (ii) a second material that reacts with the one or more carbonyl groups of the first material to add hydroxyl groups to the reaction product, where the anti-aging agent comprises a hydroxyl number of greater than about 25 mg KOH / g.
[0010] The disclosed anti-aging agents are useful for slowing or reducing the rate of aging or restoring or reviving aged asphalt binders to provide some or all of the original properties of virgin oxidized or air-blown asphalt or virgin asphalt binders used in roofing materials.
[0011] In some embodiments, the present disclosure describes an asphalt binder composition for use in producing a moisture barrier, a waterproof film, an underlay, an asphalt-based adhesive or sealant, a roofing material, an asphalt paving material, or an asphalt pavement restoration or protection material. The asphalt binder composition includes at least one of a virgin asphalt binder, an air-blown virgin asphalt binder, or a reclaimed asphalt binder material, and further includes an anti-aging agent derived from reacting an asphalt additive with one or more polyols or amine alcohols to increase the hydroxyl number of the additive, the anti-aging agent providing a less negative ΔTc in the aged asphalt containing the modified anti-aging agent after 40 hours PAV aging at 100 degrees Celsius compared to a similarly aged asphalt binder containing a non-modified asphalt additive. In some such examples, the anti-aging agent may have a hydroxyl number greater than about 25 mg KOH / g, greater than 35 mg KOH / g, greater than 40 mg KOH / g, or greater than 50 mg KOH / g.
[0012] The above summary of the present disclosure is not intended to describe each embodiment or every implementation of the present invention. The following description more particularly illustrates illustrative embodiments. In several places throughout the application, guidance is found through the recitation of examples, which examples can be used in various combinations. In each instance, the recited list serves only as a representative group and should not be interpreted as an exclusive list. Abbreviations, Acronyms, and Definitions
[0013] "Aged" refers to asphalt binders present in or recovered from reclaimed asphalt. Aged asphalt binders have a higher viscosity compared to virgin asphalt or virgin asphalt binders of the same grade as a result of aging and exposure to outside weather. The term "aged" may also include asphalt binders that have been artificially aged via the air-blown process or using the laboratory aging test methods described herein (e.g., RTFO and PAV, described further below). Aged asphalt binders may be brittle and may have a higher stiffness or a higher softening point compared to virgin asphalt binders.
[0014] "Aggregate" refers to particulate mineral materials such as limestone, granite, trap rock, gravel, crushed sand, crushed stone, crushed rock, roofing granules, and minerals that are added to asphalt binders and are useful in certain applications such as making roofing or paving applications.
[0015] "Anti-aging agent" refers to a material that can be combined with aged asphalt binder or virgin asphalt binder to slow the rate of aging of the asphalt-based material or asphalt binder, or to restore or revive the aged asphalt-based material or aged asphalt binder to provide some or all of the original properties of the virgin asphalt or virgin asphalt binder. In some embodiments, the disclosed anti-aging agents can include novel compounds or materials known to those in the art that undergo a reaction (e.g., increase in hydroxyl number) that meets the criteria disclosed herein. The effectiveness of such materials as anti-aging agents can be compared to similar aged asphalt binders without the anti-aging agent, or in examples where the starting material undergoes the disclosed modification to increase its hydroxyl number, the ΔTc value of the asphalt binder mixture containing the anti-aging agent after 40 hours of PAV aging at 100 degrees Celsius can be compared to the unmodified material.
[0016] "Asphalt paving material" or "asphalt paving mix" refers to an asphalt binder and aggregate, and optionally other components suitable for mixing the aggregate and asphalt binder.
[0017] "Asphalt binder" refers to petroleum in a strong viscous liquid or semi-solid form. Depending on the jurisdiction, the term binder can refer to "asphalt" and "asphalt binder" or "bitumen". "Bitumen" refers to a class of cementitious materials (solid, semi-solid, or viscous) of black or dark shade, composed primarily of natural or manufactured high molecular weight hydrocarbons, typically asphalt, tar, pitch, and asphaltenes. The term "asphalt binder" may be used interchangeably with the terms "binder", "asphalt", and "bitumen" in this disclosure.
[0018] The "M Critical" or "Creep Critical" grade indicates the low temperature relaxation grade of the asphalt binder. The creep critical temperature is the temperature at which the slope of creep stiffness in curvature versus creep time according to ASTM D6648 has an absolute value of 0.300. Alternatively, stiffness and creep critical temperature can be determined from 4 mm Dynamic Shear Rheometer (DSR) tests or Bending Beam Rheometer (BBR) tests.
[0019] "Modified anti-aging agent" is used to refer to a material that undergoes the disclosed process to increase the hydroxyl number of the material (e.g., increase the hydroxyl number to more than about 25 mg KOH / g). In some embodiments, the modified anti-aging agent may include a new compound not previously used in asphalt binder mixtures that undergoes the disclosed process to provide or increase the hydroxyl number and anti-aging properties. In other embodiments, the modified anti-aging agent may include a modified version of a conventional or commercially available anti-aging agent or asphalt additive that undergoes the disclosed process to provide or increase the hydroxyl number and create or increase the anti-aging properties. Thus, referring to a "modified anti-aging agent" does not mean that the starting material must be a recognized or commercially available anti-aging agent or asphalt additive before the agent undergoes the disclosed modification to increase the hydroxyl number of the material to reduce the aging rate of the asphalt binder.
[0020] "Neat" or "virgin" binder is asphalt binder that has not yet been used in or recycled from an asphalt material (e.g., asphalt paving material or asphalt shingles) and can include performance grade asphalt binder.
[0021] "Partial ester" refers to a material that contains an ester linkage and also contains either or both unreacted carboxyl groups and unreacted hydroxyl groups.
[0022] "Partial esterification" refers to an ester-forming reaction that produces one or more partial esters.
[0023] "PAV" stands for Pressurized Aging Vessel. PAV is used to simulate accelerated aging of asphalt binders as described in ASTM D6521-19a, Standard Practice for Accelerated Aging of Asphalt Binder Using a Pressurized Aging Vessel (PAV).
[0024] "Reclaimed asphalt" and "recycled asphalt" refer to RAP, RAS, and reclaimed asphalt binder derived from old pavement materials, shingle manufacturing scrap, roofing felt, and other products or applications that contain recycled asphalt binder.
[0025] "Reclaimed asphalt pavement" and "RAP" refer to asphalt that has been removed or excavated from a previously in-use asphalt pavement / road or other similar structure and processed for reuse in any of a variety of well-known ways, including milling, tearing, breaking, crushing, or grinding.
[0026] "Recycled Asphalt Shingles" and "RAS" refer to shingles from sources including roof scraps, manufacturer waste asphalt shingles, and post-consumer waste.
[0027] "Roofing asphalt binder" or "coating asphalt binder" refers to an asphalt binder suitable for making roofing materials as defined by ASTM D 3462. It has a minimum softening point of 88°C (190°F) to 113°C (235°F) and a minimum penetration of 15 dmm at 25°C (77°F).
[0028] "Roofing filler" or "filler" refers to materials, such as minerals, used in the manufacture of roofing asphalt binders. Filler materials typically have a particle size of 100-400 mesh and range from 1-80 weight percent of the total roofing asphalt binder composition.
[0029] "Roofing granules" or "granules" refers to the mineral or other material that is applied on top of roofing shingles. Granules typically have a particle size of 8 to 40 mesh.
[0030] "Roofing material" refers to materials containing an asphalt binder, including roofing shingles, rolled roofing material, built-up roofing, post-consumer waste (e.g., peeled shingles) or manufacturer discarded shingles, shingle manufacturing scrap, roofing felt, and the like.
[0031] "RTFO" stands for Rolling Thin Film Oven. RFTO is used to simulate the short-term aging of asphalt binders as described in ASTM D2872-19, Standard Test Method for Effect of Heat and Air on a Moving Film of Asphalt (Rolling Thin-Film Oven Test).
[0032] The "S-Critical" or "Stiffness Critical" grade indicates the low temperature stiffness grade of an asphalt binder. The stiffness critical temperature is the temperature at which an asphalt binder tested in accordance with ASTM D6648-08(2016) has a creep stiffness value in flexure of 300 MPa as determined by either the BBR test or the 4 mm DSR test described in ΔTc.
[0033] "SHRP" stands for Strategic Highway Research Program and its Performance Grade (PG) specifications.
[0034] "Softener" refers to a low viscosity additive that facilitates (or promotes) mixing of recycled asphalt binder and its incorporation into virgin asphalt binder during the asphalt-based material production process.
[0035] "ΔTc" refers to the value obtained when the low temperature creep or m-value critical temperature is subtracted from the low temperature stiffness critical temperature. 4mm DSR test procedures and data analysis methodologies can be used to determine the ΔTc parameter. Exemplary DSR test procedures and methodologies are also disclosed in published international applications WO2017 / 027096A2, WO2017 / 213692A1, and WO 2017 / 213693A9, the disclosures of each of which are incorporated herein by reference in their entirety. 4mm DSR test and analysis procedures are also described in Sui, C., Farrar, M., Tuminello, W., Turner, T., A New Technique for Measuring low-temperature Properties of Asphalt Binders with Small Amounts of Material, Transportation Research Record: No 1681, TRB 2010. Sui, C., Farrar, MJ, Harnsberger, PM, Tuminello, WH, Turner, TF, New Low Temperature Performance Grading Method Using 4 mm Parallel Plates on a Dynamic Shear Rheometer, TRB Preprint CD, 2011, and Farrar, M., et al,(2012), Thin Film Oxidative Aging and Low Temperature Performance Grading Using Small Plate Dynamic Shear See also Rheometry: An Alternative to Standard RTFO, PAV and BBR, Eurasphalt & Eurobitume 5th E&E Congress-2012 Istanbul (pp. Paper O5ee-467), Istanbul: Foundation Eurasphalt.The ΔTc parameter can also be determined using the BBR test procedure based on AASHTO T313 (2nd edition, 2019) or ASTM D6648-08 (2016). When the BBR test procedure is used, the test should be performed at the corresponding numerical temperature such that results with a stiffness failure criterion of 300 MPa and a creep or m-value failure criterion of 0.300 are obtained with one result below the failure criterion and one result above the failure criterion. In some instances, for asphalt binders with ΔTc values below -5°C, this may require performing the BBR test at a test temperature of 3 or higher. ΔTc values calculated from data when the requirements of the BBR criteria mentioned above are not met may not be accurate.
[0036] All weights, parts and percentages are by weight unless otherwise specified. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0037] In one aspect, the present disclosure provides an asphalt binder mixture comprising an asphalt binder and an anti-aging agent that is a reaction product of components including (i) a first material comprising a compound containing one or more carbonyl groups, and (ii) a second material that reacts with one or more carbonyl groups of the first material to add hydroxyl groups to the reaction product, where the anti-aging agent has a hydroxyl number of greater than about 25 mg KOH / g. The asphalt binder may include virgin asphalt binder, oxidized or aged (e.g., air-blown) asphalt binder, reclaimed asphalt binder material such as RAP or RAS, or a combination thereof. The disclosed anti-aging agents have been shown to reduce the rate of aging of asphalt roofing binders. Applicants have previously shown that such modified anti-aging agents can slow, reduce, or otherwise overcome some of the effects of aging in asphalt pavement to protect or preserve some or all of the original properties of the virgin asphalt binder, see published international application WO2021 / 011677A2, the disclosure of which is incorporated herein by reference in its entirety. The disclosed anti-aging agents having increased hydroxyl numbers were used with asphalt binders containing reclaimed or recycled materials, such as recycled RAP, recycled RAS, or a combination of both, to improve the aging properties of the resulting asphalt binder mix.
[0038] As asphalt-based materials age, the asphalt binders within the material oxidize, which adversely affects the properties of the asphalt material. For example, aged asphalt binders often become more brittle, especially at lower temperatures, causing the asphalt material to crack or not function as intended. Different parameters are used to measure how effectively different asphalt binders respond to aging, or how effectively different components affect the asphalt binder's response to aging. One particularly useful parameter for assessing the aging characteristics of an asphalt binder is to know the delta Tc (ΔTc) of the mixture. ΔTc can be calculated by measuring the m-critical temperature of the material and subtracting it from the S-critical temperature (e.g., ΔTc = T c,S(60s) -T c,m(60s) ). As a general and historical note to reviewers of previous literature, some of the prior literature examining ΔTc may have switched the order of subtraction, which may have changed the sign of the calculated ΔTc. For example, Anderson, R. M, King, GN, Hanson, DI, Blankenship,PB, "Evaluation of the Relationship between Asphalt Binder Properties and Non-Load Related Cracking", Association of Asphalt Paving Technologists, Volume 80, pp 615-663 (2011), based on recovered binder data from field cores, showed that ΔTc can be used to identify when an asphalt pavement has reached a point where it is at risk for non-load related mix cracking and when it has reached its potential failure limit. However, in that study, the authors subtracted the S-critical temperature from the creep or m-critical temperature, and thus, binders with poor performance characteristics would have calculated ΔTc values that were positive.
[0039] Since about 2011, industry researchers have agreed to reverse the order of subtraction, so that when the m-critical temperature is subtracted from the stiffness-critical temperature, bonds exhibiting poor performance characteristics will yield ΔTc values that are negative. The industry generally agrees that it seems more intuitive that poorly performing bonds would be more negative with decreasing performance. Thus, in the industry today, and as used herein, the ΔTc warning limit is -3°C, and the potential failure value is -5°C.
[0040] The ΔTc parameter can also be used to evaluate the effect of aging on asphalt binder properties such as the asphalt binder's relaxation characteristics (e.g., properties referred to as "low temperature creep grade"). In a field test project exposed to 40 hours of PAV aging, the ΔTc value correlated with damage to asphalt materials (e.g., asphalt pavements) associated with non-load-related block cracking, particularly top-down fatigue cracking, which is generally believed to result from loss of binder relaxation at the bituminous mix surface. Changes in the m-critical temperature can also be used to quantify the rate or extent to which the level of embrittlement of an oxidized asphalt binder increases. Similarly, determining the S-critical temperature of an oxidized asphalt binder can be used as a means of identifying changes in the stiffness properties of an oxidized asphalt binder mix at low temperatures.
[0041] It is therefore desirable to obtain an asphalt binder mix that is less susceptible to excessively negative ΔTc values occurring with aging. Many materials have been investigated with varying degrees of success to reduce or delay the impact of asphalt binder aging on the long-term performance of asphalt binder mixes. One class of materials is referred to as anti-aging agents or rejuvenation additives. These materials are often marketed with the goal of reversing the aging that has occurred in recycled raw materials such as RAP and RAS, or slowing the effects of aging in virgin binders. In some embodiments, anti-aging agents can help restore the rheological properties of aged asphalt binders, thereby allowing a greater proportion of the asphalt binder mix to be formed with RAP or RAS materials.
[0042] One group of anti-aging agents that has been explored includes sterols. Sterols, also known as steroid alcohols, are a group of organic molecules that are often derived from natural sources such as plants, animals, fungi, or bacteria. Sterols have been found to promote an increase in the ΔTc of aged binders, thereby enabling the binder to retain its performance characteristics over a longer life of the material. Sterols have shown promise as asphalt anti-aging agents, but the costs associated with producing such materials can be relatively high.
[0043] Another group of asphalt anti-aging agents includes those obtained from bio-based sources, including, for example, castor, cashew nut shell, rapeseed, soybean, sunflower, tall, vegetable and other plant-based oils. Although some of these materials may be relatively inexpensive and easy to obtain compared to sterols, many of them have been found to be poor anti-aging agents and to have other drawbacks. For example, it has been found that vegetable oils, while helpful in softening the binder, tend to leach out of the rejuvenated asphalt, causing the binder to revert to an aged state and, over time, rutting can occur in the asphalt pavement.
[0044] Published international application WO2013 / 163463A1 (Grady et al to Arizona Chemical, or "Grady"), entitled "REJUVENATION OF RECLAIMED ASPHALT", describes the use of ester-functional anti-aging agents, such as those derived from tall oil, in the production of asphalt pavements. Grady stated that the incorporation of ester functionality into the anti-aging agent reduces the onset temperature of the glass transition of the binder, which may improve the low temperature resistance and fatigue crack resistance of the asphalt, along with other properties of the asphalt pavement. However, the present inventors have found that the high ester functionality tall oil derivatives disclosed by Grady have a detrimental effect on asphalt binders, which tend to exhibit inferior performance characteristics over time than the unmodified tall oil material from which the high ester functionality derivatives were made. The inventors believe that the poor performance characteristics of the derivatives disclosed by Grady are due to the low hydroxyl content (e.g., low hydroxyl number) of the materials produced under the reaction parameters disclosed by Grady.
[0045] The presently disclosed anti-aging agents (e.g., those with increased hydroxyl numbers) can be derived from starting materials including carbonyl-containing compounds such as tall oil, other plant-based materials (e.g., plant-derived raw materials or extracts), or other asphalt additives that undergo reaction with a second material that can react with the carbonyl groups to add hydroxyl groups to the reaction product, resulting in a hydroxyl number of greater than about 25 mg KOH / g. Without being bound by theory, it is believed that increasing the number of free hydroxyl groups in such agents, for example by increasing the number of free hydroxyl groups in the tall oil material, increases the polarity of such materials, making them more compatible and therefore more suitable for facilitating softening and mixing with aged asphalt binders and other materials. For example, asphalt binders are complex mixtures of materials, and although the mechanism of aging is not fully understood, there is a general shift in the relative amount of aliphatic groups or segments of the binder material to more polar structures due to oxidation, which includes, for example, the formation of ether, peroxide, and alcohol groups within the aged binder material. This shift causes the binder to become harder and more polar over time. The inventors have found that increasing the polarity of starting materials such as tall oil or other carbonyl-containing agents by increasing the relative number of free hydroxyl groups in such compounds can significantly increase their effectiveness as asphalt binder aging inhibitors. The resulting aging inhibitors appear to be more compatible with aged asphalt binders and may help to solvate and soften the aged asphalt binders, lowering the m-critical and S-critical grades of the material as well as increasing the ΔTc of the asphalt binder mixture. The modified aging inhibitors may help to produce functional asphalt binder mixtures, in part, by softening the aged asphalt binders, thus allowing the mixtures to be easily prepared, paved, and compacted. Additionally or alternatively, the modified anti-aging agents may help slow or prevent the aging effects of virgin asphalt binders, allowing them to be used for a longer service life.
[0046] The disclosed modified anti-aging agents can alter (e.g., reduce or delay) the aging rate of asphalt binders, or rejuvenate, restore, or revive aged or reclaimed asphalt binders to provide some or all of the properties of virgin asphalt binders. The disclosed asphalt binder compositions or mixtures containing the disclosed anti-aging agents with increased hydroxyl numbers can also improve the processing and performance properties of virgin, reclaimed, and highly oxidized asphalt, thereby helping to protect, recycle, and reuse asphalt sources or asphalt binders. In some embodiments, the disclosed anti-aging agents can alter or improve the physical and rheological properties of asphalt binder mixtures, such as stiffness, effective temperature range, and low temperature properties. Such asphalt binder mixtures containing the disclosed anti-aging agents may be useful in producing a variety of asphalt-based materials, including, but not limited to, moisture barrier and waterproof films, underlayments, asphalt-based adhesives and sealants, roofing materials (such as roofing shingles, roll roofing materials, and built-up roofing), asphalt paving materials, asphalt pavement restoration or protection materials, and the like.
[0047] Starting materials that can be used to derive the disclosed anti-aging agents include one or more compounds containing accessible or available carbonyl groups that can be reacted with a second material (e.g., a polyol or an amine alcohol) to increase the number of free hydroxyl groups in the reaction product such that the hydroxyl number of the resulting product is greater than about 25 mg KOH / g. Such starting materials can include those that react with a polyol (e.g., to form an ester bond) or with an amine group of an amine alcohol (e.g., to form an amide bond) and contain a carboxylic acid group, an ester group, an amine group, an imide group, or combinations thereof. Exemplary carbonyl-containing compounds include glycerides and triglycerides, such as various vegetable and natural oils, various tall oils, vegetable oils, rosin, pitch, wood chemicals, engine oils, regenerated oils, fatty acids, monoacids, diacids, triacids, C1-C2 acidic acids, and the like. 36 The starting materials may include, but are not limited to, carboxylic acids, esters, keto acids, oxocarboxylic acids, polyesters, anhydrides, compounds containing both anhydride and carboxylic acid groups, various amides and imides, compounds containing two or more of the above referenced types of groups, blends thereof, and the like. Additionally or alternatively, the starting material may include mixtures or blends of different carbonyl-containing compounds, and additionally or alternatively, include co-reactants that do not contain carbonyl groups but may participate in the reaction. Although the examples below focus primarily on tall oil as a starting material (e.g., first material), the concepts disclosed herein are not limited to tall oil.
[0048] Preferred starting materials include those with one or more reactive carbonyl groups (e.g., carboxylic acids, esters, amides, imides, etc.) and that are relatively inexpensive to obtain. Such preferred starting materials may include, but are not limited to, plant-based materials such as castor, cashew nut shells, cottonseed, corn, peanuts, rapeseed, rice bran, safflower, sarsaparilla root, soybean, sunflower, vegetable, wheat germ, other plant-based oils; recycled oils; rosin and rosin acids; fatty acids; mixtures thereof, and the like. Additionally or alternatively, the starting materials may include one or more coal or petroleum-based materials, including, but not limited to, coal tar pitch, coal extracts, petroleum-derived reactants, derivatives or mixtures thereof, and the like. The disclosed modification techniques can also be applied to other commercially available asphalt additives, including conventional anti-aging agents, and where such agents and additives can react with one or more hydroxyl groups of the polyol or amine groups of the amine alcohol to provide a modified anti-aging agent or additive of sufficient hydroxyl functionality to impart improved anti-aging properties to the asphalt binder mixture. In some embodiments, the available carbonyl groups in the starting material can be increased through an oxidation process or other synthetic techniques.
[0049] The relative number of free hydroxyl groups in the starting material can be increased using various techniques. In some embodiments, the number of free hydroxyl groups can be increased by reacting the carbonyl-containing starting material with one or more polyols or amine alcohols, while controlling the reaction conditions and stoichiometric ratios of the materials that favor the addition of such polyols or amine alcohols without undue consumption or depletion of available hydroxyl groups. Additionally or alternatively, the hydroxyl value of the starting material can be increased through alcoholysis-transesterification reactions, or by using different reaction mechanisms, catalysts, or by using different reactants. The goal in each such example is to achieve partial esterification while leaving unreacted (i.e., free) hydroxyl groups in the reaction product.
[0050] The availability of free hydroxyl groups can be measured in terms of the hydroxyl value of the resulting compound, for example, by using ASTM method D1957-86 (1995). The disclosed anti-aging agents, after reaction with polyols or amine alcohols, should have a resulting hydroxyl value of greater than about 25 mg KOH / g, more preferably at least about 35 mg KOH / g, and most preferably at least about 50 mg KOH / g. For comparison, commercially available fatty acid esters and rosin acid esters typically have hydroxyl values in the range of 0-5 mg KOH / g and 5-12 mg / KOH / g. Unrefined tall oil has a hydroxyl value of around 1 mg KOH / g.
[0051] The final hydroxyl number can be adjusted as needed to higher or lower values to obtain the desired adjustment to ΔTc depending on the final needs of the disclosed binder mix. In some embodiments, the disclosed anti-aging agents have a less negative hydroxyl number ΔTc in aged asphalt containing the anti-aging agent after 40 hours PAV aging at 100 degrees Celsius compared to a similarly aged binder containing unmodified agent.
[0052] In some embodiments, the final hydroxyl value may be adjusted based on the number of acid groups available in the starting material (e.g., the first material), the number of hydroxyl groups in the second material (e.g., the selected polyol or amine alcohol), the initial polarity of the reactants, etc., depending on the acid value of the starting materials. The disclosed modification process may, in some embodiments, reduce the acid value of the starting material. For example, reacting the fatty acid material with one or more polyols or amine alcohols may cause at least a portion of the carbonyl groups of the fatty acid to react with the polyol (e.g., by esterification) or amine alcohol (e.g., by amide formation) to result in a lower resulting acid value of the material. In some embodiments, the disclosed anti-aging agents may have an acid value of less than about 100, less than about 70, less than about 30, or even less. In some embodiments, the acid value of the starting material may be initially increased to provide more reactive acid groups in the starting material for combining with the disclosed polyols or amine alcohols. The acid value of the starting material may be increased using a variety of techniques. For example, the starting material may contain or react with an acid or anhydride (e.g., acrylic acid, adipic acid, fumaric acid, maleic acid, maleic anhydride, succinic acid, neodecanoic acid, other diacids, etc.) to increase the number of carboxylic acid groups of the starting molecule, for example, by Diels-Alder or ester addition. The increase in available carboxylic acid groups may allow additional bonding between a second material (e.g., polyol or amine alcohol) used to increase the hydroxyl number of the resulting product. Additionally or alternatively, at least a portion of the available carboxylic acid groups of the starting material may remain within the resulting modified anti-aging agent to perform other functions, for example, in the asphalt binder mixture. For example, the carboxylic acid groups may aid in the mixing of the asphalt binder with the aggregate and facilitate bonding therewith.
[0053] In some embodiments, the disclosed modification process can include an alcoholysis-transesterification process to increase the hydroxyl value. For example, a starting material (e.g., soybean oil or other vegetable-based oil) containing one or more ester bonds can be reacted with a polyol using a transesterification catalyst. A polyol with more than two hydroxyl groups can replace an organic group with an ester bond. One of the hydroxyl groups of the polyol is donated to the removed organic group to form a new alcohol that may be removed but remain in the reaction product. The polyol (without a hydroxyl group) forms a new ester bond with the deesterified carbonyl group (without a removed organic group) in the modified starting material, resulting in one or more additional free hydroxyl groups.
[0054] In some embodiments, the starting material can be an unrefined or refined material, for example, the starting material can be a low cost, pure or impure by-product, or a waste stream from the manufacture of a higher value product.
[0055] In some embodiments, the disclosed anti-aging agent may include modified tall oil. Conventional tall oil is a by-product of papermaking and contains a complex mixture of different compounds including various rosin and fatty acid materials, including rosin acids such as abietic acid and its isomers; various fatty acids including palmitic acid, oleic acid, and linoleic acid; fatty alcohols; sterols; and other alkyl hydrocarbon derivatives. The composition of tall oil varies greatly depending on the source, level of refinement, etc. A typical technique for quantifying the quality or refinement of tall oil is to refer to the acid number, fatty acid content level, or both. Conventional tall oil can be purchased with acid numbers ranging from about 100 to 200 or about 125 to 165. Tall oil is available in many forms including, for example, crude tall oil and distilled or improved crude tall oil. Distillation of crude tall oil results in various isolated forms of fatty acids, which are highly saturated and volatile long chain fatty acids known as tall oil heads, C8-C10 fatty acids with various degrees of unsaturation. 20Tall oil fatty acids, including fatty acids, and mainly C 18 ~C 20 and tall oil rosin or pitch, which contains tricyclic monocarboxylic acids of the formula: 1. Commercially distilled tall oil contains a mixture of mainly tall oil fatty acids and tall oil rosin in various proportions. In some embodiments, the disclosed anti-aging agents may be derived from crude tall oil, distilled tall oil, tall oil heads, tall oil pitch, or mixtures thereof.
[0056] The hydroxyl value of tall oil, particularly of such fatty acids, rosin acids, and similar compounds present in tall oil, can be increased by reacting tall oil with polyols or amine alcohols at relatively low temperatures. The hydroxyl or amine groups can react with one or more carbonyl groups (e.g., carboxylic acid groups) of the fatty acids and rosin acids of tall oil to form ester or amide bonds. While the reaction conditions, times, and stoichiometry can be unique to the individual carbonyls and polyols used in the reaction, the reaction rate can be controlled to favor the addition of such polyols or amine alcohols while promoting the retention of a large amount of residual hydroxyl groups through control of reaction temperature and stoichiometric ratios. The disclosed reaction can be carried out at relatively low temperatures and without an ester catalyst, helping to ensure that available hydroxyl groups are not consumed by subsequent crosslinking side reactions, thereby ensuring high hydroxyl values in the resulting compounds.
[0057] For reactions using polyols and fatty acids, the reaction temperature can be below 200° C. Temperatures above 200° C. can promote the formation of ester groups, significantly reducing the hydroxyl value of the resulting compound.
[0058] For reactions using amine alcohols and fatty acids, the reaction temperature may be high enough to favor amide reactions (e.g., about 150° C.), but is generally lower than reaction temperatures that favor esterification (e.g., greater than about 180° C.). Temperatures greater than 200° C. can promote the formation of ester groups, significantly reducing the hydroxyl value of the resulting compound.
[0059] Higher molecular weight starting materials (e.g., rosin acids and higher molecular weight acids) and ester-based starting materials (e.g., polyesters, vegetable oils, triglycerides, etc.) may require higher reaction temperatures, longer reaction times, or reaction catalysts to react with the disclosed polyols or amine alcohols compared to the lower molecular weight fatty acids discussed above.
[0060] The second material used to react with one or more carbonyl groups of the first material to increase the number of hydroxyl groups in the reaction product can include polyols, amine alcohols, and the like. Suitable polyols and amine alcohols can include, but are not limited to, polyols containing two or more free hydroxyl groups or amines containing one or more hydroxyl groups, such as ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dimethylolpropionic acid, glycerin, trimethylolpropane, neopentyl glycol, pentaerythritol, dipentaerythritol, sorbitol, sucrose, polyethylene glycol, polypropylene glycol, methanolamine, dimethylethanolamine, ethanolamine, aminomethylpropanol, polysulfide polyols, propanolamine, mixtures thereof, and the like. In some embodiments, the source of hydroxyl groups can include polyalkylene ether polyols, such as polyethylene glycol (PEG), polytetramethylene ether glycol, polypropylene glycol, or similar ether polyols with multiple available hydroxyl groups. Additionally or alternatively, the source of hydroxyl groups can include polyalkylene polyols, such as polybutadiene diols. In some embodiments, the source of hydroxyl groups can include raw or refined materials. For example, the source of hydroxyl groups can be a low-cost, pure or impure by-product or waste stream resulting from the manufacture of higher value products (e.g., glycerin obtained in the production of ethanol from grains).
[0061] Exemplary polyalkylene glycols include repeating units of ethyl oxide, propyl oxide, or butyl oxide that are miscible, soluble, or dispersible in the starting material and have low to high molecular weights, e.g., number average molecular weights of about 190 to about 8000 g / mol, preferably greater than about 190 g / mol. Such polyalkylene glycols may include liquids, such as PEG 300 and PEG 400, available from Dow Chemical Co. as CARBOWAX™ PEG 300 and CARBOWAX PEG 400, respectively; waxes; solids; or combinations thereof. Polyethylene polyols represent a preferred class of polyols that, when reacted with starting materials such as tall oil, result in modifiers that exhibit comparable rejuvenation properties at lower hydroxyl numbers compared to other polyols tested. Without being bound by theory, it is believed that the long chain polyether linkages in such materials may also serve to increase the polarity of the resulting anti-aging agent, making the modified anti-aging agent more compatible with aged asphalt binders and possibly retarding the aggregation of oxidized molecules of the aged binder.
[0062] In some examples, the disclosed anti-aging agents can be prepared by reacting one or both of the reaction components (e.g., a first material containing a carbonyl group, a second material contributing a hydroxyl group, or both) with a third material (e.g., a co-reactant) to produce an anti-aging agent reaction product. The third material can contain one or more unsaturated groups configured to react and bond with at least one of the other starting materials in producing the resulting reaction product. The third material can be used to modify the physical properties of the resulting reaction product, for example, by increasing the molecular weight of the reaction product to modify the flash point of the product or to help reduce the manufacturing cost of the reaction product. The third material can contain either carbonyl or hydroxyl groups, or neither. Materials that can be used for the third material include, but are not limited to, unsaturated alcohols such as dicyclopentadiene (DCPD), piperylene, isoprene, or aliphatic alcohols. For example, starting materials such as soybean oil or tall oil, maleic anhydride, and DCPD can be first reacted together and then reacted with one or more polyols or amine alcohols to result in a resulting reaction product having a hydroxyl number greater than about 25 mg KOH / g. Other usable reactions can include the Diels-Alder reaction between DCPD, styrene, an unsaturated acid or anhydride; DCPD and a vegetable oil or vegetable-based oil; a vegetable oil or vegetable-based oil reacted with maleic anhydride, fumaric acid, adipic acid, neodecanoic acid, or acrylic acid; rosin acid reacted with maleic anhydride, etc. The reaction can be carried out as a stepwise production of reaction products or as a single reaction scheme.
[0063] In some embodiments, the disclosed anti-aging agents can maintain a ΔTc value of greater than or equal to -5°C as the asphalt or asphalt pavement ages. In some embodiments, the disclosed anti-aging agents can result in asphalt binders with a ΔTc of greater than or equal to -5°C, more preferably greater than or equal to -3°C, after 40 hours of PAV aging at 100°C. In some embodiments, the disclosed anti-aging agents result in asphalt binders with positively greater ΔTc values and reduced R-values after aging when compared to similarly aged asphalt binders without the disclosed anti-aging agents, or aged binders made using similar but unmodified materials or anti-aging agents with lower hydroxyl numbers.
[0064] Additionally or alternatively, the disclosed modified anti-aging agents can modify, reduce, or delay the degradation of rheological properties of binders containing recycled bituminous materials such as RAS and RAP. The disclosed anti-aging agents can be added to asphalt binder mixtures at about 0.5 to about 15 wt%, or about 1 to about 10 wt%, or about 1 to about 3 wt%, based on the total amount of binder present.
[0065] The disclosed anti-aging agents have not been previously used as resistive agents in the asphalt industry, but may be derived from novel materials modified to have the disclosed high hydroxyl numbers (e.g., greater than about 25 mg KOH / g, greater than 35 mg KOH / g, greater than 40 mg KOH / g, or greater than 50 mg KOH / g) to provide the desired ΔTc as disclosed herein. Such novel compounds may include polyols, aliphatic modified polyols, polyester polyols, polycarbonate polyols, and the like.
[0066] The disclosed anti-aging agents can be combined with any suitable source of asphalt binder material. In some embodiments, the asphalt binder mixture can include virgin asphalt binder, oxidized asphalt binder, asphalt binder derived from reclaimed asphalt, or combinations thereof. Due to its high asphalt binder content, RAS is an attractive component for reclamation and reuse. RAS has an asphalt binder content ranging from 15-35 wt%, for example, compared to RAP, which may have an asphalt content of about 5 wt%. Generally, there are two main types of RAS materials, including peel-apart roofing shingles and roofing shingle tabs (also referred to as manufacturer's waste). Peel-apart roofing shingles are produced during demolition or replacement of an existing roof, while roofing shingle tabs are produced when new asphalt shingles are scraped off while being produced to the required physical dimensions. The quality of peel-apart roofing shingles can vary considerably due to their exposure to the environment. The disclosed anti-aging agents have been shown to improve the high and low temperature properties, and the PG grades at both low and high temperature ends, of RAS-containing asphalt binder mixtures, such as those produced from peel-apart roofing shingles.
[0067] As one skilled in the art will recognize, the disclosed anti-aging agents may be used in a wide variety of applications in the production of asphalt-based materials. The disclosure that follows focuses primarily on the use of such asphalt binder mixtures in the production of roofing materials (e.g., roofing shingles, roofing rolls, built-up roofing, etc.). However, such asphalt binder mixtures need not be limited to such applications, and are contemplated for use in other applications, including, but not limited to, asphalt pavement, asphalt pavement maintenance (e.g., asphalt pavement repair or preservation) products, underlays, asphalt-based adhesives and sealants, asphalt-based moisture barriers or films, asphalt-based coating materials, and the like.
[0068] Roofing materials can include roofing shingles, rolled roofing materials, and built-up roofing. Such roofing materials can be constructed using substrate materials such as fiberglass mats, asphalt binder-based coating mixtures, and a layer of granules embedded in the top coating. The substrate mat can be saturated with a hot saturant asphalt binder composition, which can then be coated on both sides (e.g., top and bottom) with additional asphalt binder, and finally topped with a top layer of granules. As used herein, the term "top" refers to the side that faces up or away from the roof when the roofing material is installed on a roof, and "bottom" refers to the side that faces down or toward the roof.
[0069] At least one of the saturant, top, and bottom asphalt coating compositions can be comprised of the disclosed anti-aging additive-containing asphalt binder mixture, and the asphalt binder compositions of the different layers need not be the same. Since most of the aging occurs within the top asphalt layer due to the layer being in a position directly exposed to sunlight, it may be desirable for at least the top asphalt coating composition to include the disclosed anti-aging additive.
[0070] The substrate mat for the roofing material may be of any type known for use in reinforcing asphalt binder-based roofing materials, including, but not limited to, webs of fibrous materials, such as nonwoven mats of fiberglass, mineral fibers, cellulose fibers, rag fibers, synthetic fibers such as polymeric fibers, or mixtures thereof, scrims, or felts. In some embodiments, the substrate may be an organic material, such as a felt mat produced from cellulose fibers, or a glass-based mat produced from glass fibers. In some embodiments, the roofing shingles produced are of the organic felt type.
[0071] The top surface of the coating asphalt binder may include roofing granules either coated on or embedded within. The roofing granules are intended to contribute to the desired weather resistance, fire resistance, visually decorative exterior, or any combination thereof. In some embodiments, the granules are crushed and screened mineral materials, which are then coated or embedded with the top asphalt binder coating composition. In some embodiments, the granules are hard mineral rocks, such as slate, basalt, nephelite, and the like. In some embodiments, the granules may be the same type of granules or a mixture of different types, textures, shapes, and / or colors of granules. The granules may also include coating granules (e.g., ceramic coatings, infrared reflective coatings, or colored coatings), or additives (e.g., copper compounds). Suppliers of roofing granules include 3M, GAF, and Harsco Minerals.
[0072] An asphalt binder composition suitable for making roofing materials is generally produced by selecting a suitable asphalt binder and processing the asphalt binder to obtain properties useful as roofing materials. For example, roofing asphalt binders usually retain a certain degree of hardness and do not flow under high temperature conditions generated by exposure to sunlight. Such increased hardness is generally accompanied by a reduced level of penetration, an increased viscosity, and an increased softening point.
[0073] In some embodiments, it is desirable to include aged asphalt binders in the context of roofing applications. Aging the asphalt binder can modify the physical properties of the asphalt binder, for example, to increase the softening point (e.g., target softening point from about 85° C. (185° F.) to about 99° C. (210° F.)) and help increase the roofing material's ability to withstand roof flow at high temperatures, reduce the penetration of the shingles without becoming too brittle (e.g., target penetration of about 15 dmm), adjust the melt viscosity to a suitable range, and generally improve the binder's ability to withstand exposure to sun, high temperatures, and inclement weather conditions.
[0074] In some embodiments, aging the binder can be accomplished by an "air-blown" process in which air is blown through the molten asphalt binder for several hours (e.g., from about 1 hour to about 72 hours) to intentionally oxidize the binder in order to modify the physical properties of the asphalt binder, such as increasing the softening point of the asphalt mix. The length of time depends on a variety of factors, such as the type of asphalt binder raw material used, the processing temperature, air flow rate, the design of the processing equipment, and the desired properties of the resulting asphalt binder coating. Additionally or alternatively, using binder extracted from RAS or RAP provides a convenient source of aged binder material for roofing applications.
[0075] General specifications for roofing materials are set forth in ASTM D225-07 ("Asphalt binder Shingles (Organic Felt) Surfaced into Mineral Granules," American Society for Testing and Materials, Annual Book of ASTM Standards, Volume 04.04, West Conshohocken, PA, 1996); and ASTM D3462M-19 ("Asphalt binder Shingles Made From Glass Felt and Surfaced with Mineral Granules." American Society for Testing and Materials, Annual Book of ASTM Standards, Volume 04.04, West Conshohocken, PA, 1996). Additional properties of the roofing asphalt binder composition can be measured by any suitable test known in the art, including, but not limited to, softening point, or "SP", per ASTM D36M-14(2020); penetration power, or "pen", per ASTM D5M-20 run at 25°C; melt viscosity, per ASTM D4402M-15 run at 204°C (400°F) using a Model RV Brookfield Viscometer, spindle #18, 6 RPM, or a Model RV Brookfield Viscometer, spindle #21, 50 RPM; durability, per ASTM D4798M-11(2019); flash point, per ASTM D92-18; and stability, per ASTM D3791M-11(2018) modified to run at an oven temperature of 260°C (500°F) for up to 5 days, or similar test procedures.
[0076] In some embodiments, an asphalt binder composition configured to produce a roofing material can include a blend of binder materials including about 75 wt% to about 95 wt% virgin binder and about 5 wt% to about 25 wt% binder extracted from recycled asphalt, such as RAS. The binder blend can be further processed (e.g., air blown) as desired. Newly manufactured shingles can have a total binder content of about 15 to about 35 wt%, for example about 20 wt%.
[0077] The disclosed anti-aging agents can be added to the above asphalt binder mixtures, including those containing aged asphalt binders recycled or extracted from RAS or RAP, intentionally oxidized / aged (e.g., air-blown) asphalt binders, virgin asphalt binders, or mixtures thereof, to produce newly manufactured roofing materials. Adding the disclosed anti-aging agents to virgin asphalt binders, oxidized asphalt binders, recycled asphalt binders, or combinations thereof, and using the resulting asphalt binder mixtures used to manufacture one or more of the disclosed roofing materials, may modify or inhibit the degradation or rheological properties of the aged binders and improve the service life of the roofing materials. For example, the disclosed anti-aging agents can improve the high temperature stiffness, effective temperature range, and low temperature stiffness, and / or relaxation properties of the asphalt binder.
[0078] The disclosed asphalt binder mixtures can be prepared by heating and mixing or blending together the disclosed anti-aging agents, binder source (e.g., virgin, oxidized, RAS, RAP, or combinations thereof), and other optional additives to form a mixture. One skilled in the art will recognize that many orders of component addition and mixing are possible. In one aspect, a method for improving the aging characteristics of an asphalt binder involves mixing or blending the disclosed anti-aging agents with an asphalt binder at a temperature of about 100°C to about 250°C. In some embodiments, the disclosed anti-aging agents are mixed with the asphalt binder at a temperature of about 125°C to about 175°C, or 180°C to 205°C.
[0079] In some embodiments, the disclosed asphalt binder composition may also include other materials (e.g., additives) in addition to the disclosed aging inhibitors, such as antioxidants, adhesion promoters, fillers, polymers, pigments, stabilizers, solvents, waxes, and other materials. The types and amounts of such additives are familiar to those skilled in the art. Additives may be selected based on the intended use (e.g., producing a hot-applied asphalt film), anticipated environment, performance characteristics, and the like. Useful polymers may include, for example, ethylene-vinyl acetate copolymers, polybutadiene, ethylene-propylene copolymers, ethylene-propylene-diene terpolymers, reactive ethylene terpolymers (e.g., ELVALOY™), butadiene-styrene block copolymers, styrene-butadiene-styrene (SBS) block copolymers, isoprene-styrene block copolymers, and styrene-isoprene-styrene (SIS) block copolymers, chloroprene polymers (e.g., neoprene), and the like. Cured elastomeric additives may include rubber materials of ground-bearing tires. See, e.g., 2015 Standard Specifications for the State of California, Section 37, pg. 423, and Section 39, Hot Mix Asphalt, beginning on pg. 447, also available at http: / / www.dot.ca.gov / dist1 / d1lab / SECTION%2039%20%20HMA.pdf and http: / / caltrans-opac.ca.gov / publicat.htm.
[0080] The disclosed binder composition may also include one or more fillers in an amount of about 1-80 wt%, 45-60 wt%, 50-75 wt%, or 60-80 wt%, based on the weight of the coating composition. In some embodiments, the filler is a sedimentary rock or mineral particle, such as limestone or calcium carbonate, dolomite, silica, talc, shale, clay, mica, sedimentary rock particle, or a combination thereof. Other suitable fillers include fly ash, carbon black, and inorganic fibers, or a combination thereof. The filler may include one or more of the top, bottom, or mat coating layers. In some embodiments, the filler functions to impart desired mechanical properties to the roofing material, such as shingles, reduce raw material costs, or both. The disclosed roofing material may also include an inorganic or organic agent (e.g., silica sand) in the bottom asphalt coating to aid in packaging and help prevent individual shingles from sticking to each other during shipping.
[0081] The present application is further illustrated in the following non-limiting examples in which all parts and percentages are by weight unless otherwise indicated. Example 1
[0082] The characteristics of bitumen-containing binders in recycled asphalt sources compared to virgin binders used in asphalt binder mixes are shown in Table 1. [Table 1]
[0083] The data in Table 1 show that typical virgin binders produced at refineries can retain a ΔTc above -3°C even after 40 hours of PAV aging. Additionally, the data in Table 1 show that RAP-recovered binders can have ΔTc values below -4°C and that the impact of high levels of RAP in new bitumen mixes can further reduce the ΔTc values. Furthermore, the extremely negative ΔTc values of the RAS-recovered binders call for additional scrutiny of the overall impact of incorporating RAS into bitumen mixes.
[0084] RAS asphalt binders are typically very hard, especially with oxidation; therefore, RAS is expected to have a higher degree of ΔTc impact than that experienced with RAP asphalt binders. Calculating ΔTc for RAS asphalt binders can be more complicated than for RAP asphalt binders due to the difficulties of BBR analysis. The table below presents estimated ΔTc data from RAS binders in National Center for Asphalt Technology (NCAT) Report 16-01, reported in TRB E-Circular 241, and additional data obtained from AI IS 240. Table 2: Predicted ΔTc for RAS Binders [Table 2] Example 2
[0085] Preparation of crude tall oil modified anti-aging agents: Two representative modified anti-aging agents were prepared using crude tall oil and either PEG400 or glycerin as the source of hydroxyl groups.
[0086] Sample 1 was prepared using 680 grams of crude tall oil having an acid number of about 160 and a hydroxyl number of about 1 mg KOH / g as determined by ASTM D1957-86 (1995). The crude tall oil was heated to about 70°C to facilitate mixing, followed by the addition of about 320 grams of PEG 400 (polyethylene ether glycol with a molecular weight of 400 g / mol). The contents of the flask were heated to 180°C to initiate a small amount of esterification reaction (i.e., partial esterification) to attach the PEG to the tall oil compound, but to prevent the hydroxyl groups from being fully consumed in the reaction. Additionally, no esterification catalyst was used in the reaction to limit the degree of esterification that occurred. The reaction was held at elevated temperature until an acid number of 65-85 was obtained. The resulting modified anti-aging agent was a sample with a hydroxyl number of about 35-60 mg KOH / g, which is a partial ester.
[0087] Sample 2 was prepared using 785 grams of crude tall oil having an acid number of about 160 and a hydroxyl number of about 1 mg KOH / g as determined by ASTM D1957-86 (1995). The crude tall oil was heated to about 70°C to facilitate mixing, followed by the addition of about 215 grams of glycerin. The contents of the flask were heated to 180°C to initiate a small amount of esterification reaction to attach the glycerin to the tall oil compounds. No esterification catalyst was used in the reaction to limit the extent of esterification that occurred. The reaction was held at elevated temperature until an acid number of 50-70 was obtained. Based on the stoichiometry and reaction conditions, it was expected that the glycerin would bind with the tall oil such that only about 1-1.25 of the three glycerin hydroxyl groups would react, allowing about 1.75-2.0 hydroxyl groups to remain free. The resulting modified anti-aging agent has a hydroxyl number of about 45-75 mg KOH / g. Example 3
[0088] To investigate the efficacy of the modified anti-aging agent of Example 2, five asphalt binders were prepared and aged under various conditions. The binders were prepared by mixing the ingredients in a one-gallon can low shear LIGHTING™ mixer at temperatures between 187.8°C and 204°C (370°F and 400°F) for approximately 30 minutes.
[0089] Binder 1 consisted only of virgin binder PG64-22.
[0090] Binder 2 contained 96% PG64-22 mixed with 4% modified anti-aging agent sample 1.
[0091] Binder 3 contained 92% PG64-22 mixed with 8% Modified Anti-Aging Agent Sample 1.
[0092] Binder 4 contained 96% PG64-22 mixed with 4% Modified Anti-Aging Agent Sample 2.
[0093] Binder 5 contained 92% PG64-22 mixed with 8% Modified Anti-Aging Agent Sample 2.
[0094] The high and low temperature properties of the resulting binders were measured using the 4 mm DSR test procedure for unaged, RTFO aged samples according to AASHTOT-240, and PAV aged samples according to AASHTOR 28 at 100°C for 20 hours. The results are shown in Table 3. [Table 3]
[0095] The temperature at which the binder P / F is heated in the non-aged condition is the temperature at which the binder stiffness is equal to approximately 1 kilopascal (kPa) when tested according to AASHTO T-315. The temperature at which the binder P / F is heated in the RFTO aged condition is the temperature at which the binder stiffness is equal to approximately 2.2 kPa when tested according to AASHTO T-315. The temperature at which the binder P / F is heated in the RFTO aged condition is the lower temperature at which the binder stiffness is equal to approximately 5000 kPa when tested according to AASHTO T-315. The results in Table 3 show that when no anti-aging agent is present in the sample, the P / F temperature increases at a faster rate than when the modified anti-aging agent is present.
[0096] ΔTc values were also measured using the low temperature BBR test according to AASHTO T-313 for PAV aged samples aged at 100°C for 20 and 40 hours. The results for the 20 and 40 hour aged samples are shown in Tables 4 and 5, respectively. [Table 4] [Table 5]
[0097] For binder 1, which did not contain the presence of anti-aging agent, the low temperature ΔTc in the BBR test was relatively lower than either of the sample binders containing modified anti-aging agent of samples 1 or 2. All binder samples containing modified anti-aging agent tested exhibited a more positive ΔTc. All ΔTc values for the 20 hour PAV aged binder samples with modified anti-aging agent were positively greater compared to pure PG64-22, which exhibited a ΔTc of -1.1. The ΔTc values of the 40 hour PAV aged binder samples with modified anti-aging agent also showed superiority over pure PG64-22 with a ΔTc of -3.9 compared to the lowest ΔTc of -1.8 for the binder samples containing modified anti-aging agent.
[0098] The data summarized in Tables 3-5 show that modified anti-aging agents with high hydroxyl numbers had a significant positive impact on both the flexibility of the aged binder samples and the critical relaxation properties related to the m-value. Example 4
[0099] Preparation of soybean oil as a modified anti-aging agent by alcoholysis-transesterification: Approximately 800 grams of soybean oil are added to a laboratory flask. The flask is heated to approximately 70°C to facilitate mixing. Approximately 100 grams of glycerin and 5 grams of transesterification catalyst (lithium ricinoleate) are then added to the flask. The contents of the flask are heated to approximately 250°C for 2 hours, then heated to approximately 270°C and held for 10 hours. The material is then steam sparged to remove any unreacted glycerin. The resulting compound had a hydroxyl number of greater than 100 mg KOH / g of sample. Example 5
[0100] Preparation of tall oil modified anti-aging agent with amine alcohol: Approximately 800 grams of sample 2 material, with a hydroxyl value of 45-75 mg KOH / g, was added to a laboratory flask and heated to approximately 70°C to facilitate mixing. Approximately 20 grams of monoethanolamine was added to the flask. The contents of the flask were heated to approximately 140°C and held for 2 hours to facilitate amide formation. The resulting material was then steam sparged to remove any unreacted monoethanolamine. The lower temperature reaction facilitates amide formation while minimizing ester formation, thereby protecting the hydroxyl groups. The resulting compound had a hydroxyl value of greater than 50 mg KOH / g. Example 6
[0101] Modification of Tall Oil with Amine Alcohol Preparation of Antiaging Agent: Approximately 800 grams of crude tall oil with an acid value of about 160 was added to a laboratory flask. The flask was heated to 70°C to facilitate mixing, followed by the addition of approximately 100 grams of monoethanolamine. The contents of the flask were heated to 140°C and held for 3 hours to facilitate amide formation. The material was then steam sparged to remove any unreacted monoethanolamine. The lower temperature reaction facilitates amide formation while minimizing ester formation, thereby protecting the hydroxyl groups. The resulting compound has an acid value of about 60-90 and a hydroxyl value of greater than 65 mg KOH / g. Example 7
[0102] Preparation of tall oil modified anti-aging agent with polyol: Approximately 785 grams of unrefined tall oil with an acid value of about 160 and a hydroxyl value of about 1 was added to a laboratory flask and heated to about 70°C to facilitate mixing. Approximately 24 grams of maleic anhydride was added to the flask. The contents of the flask were heated to about 205°C and held for 2.5 hours to encourage the formation of the Diels-Alder adduct. The contents of the flask were then cooled to about 180°C, followed by the addition of about 235 grams of glycerin to initiate a slight level of esterification reaction to bond the glycerin to the tall oil adduct, but to prevent the hydroxyl groups from being fully consumed in the reaction. This temperature initiates a slight level of esterification reaction while also maintaining the final hydroxyl content. Additionally, no esterification catalyst was used in the reaction to limit the degree of esterification that would occur. The reaction was held at the elevated temperature until an acid value of 70-90 was obtained. The resulting sample modified anti-aging agent has a hydroxyl number of about 60-95 mg KOH / g of the sample. Example 8
[0103] Preparation of tall oil modified anti-aging agent with polyol: About 785 grams of unrefined tall oil with an acid value of about 160 and a hydroxyl value of about 1 was added to a laboratory flask and heated to about 70°C to facilitate mixing. About 315 grams of glycerin was added. The contents of the flask were heated to 180°C and held for about 1.5 hours. The reaction mass was then heated to about 235°C and held for 1 hour. The reaction mass was then heated to 270°C and held to an acid value of less than about 10. The resulting sample modified anti-aging agent had a hydroxyl value of about 60-100 mg KOH / g sample. Example 9
[0104] Preparation of soybean oil modified anti-aging agent: A mixture of soybean oil and glycerin was reacted to create an initial reaction product. The initial reaction product was then further reacted with rosin acid at about 235°C and held for 1 hour. The reaction mass was then heated to 250-280°C and held to an acid value of about less than 10. The resulting sample modified anti-aging agent had a hydroxyl value of about 60-100 mg KOH / g sample.
[0105] The starting materials, polyols, and amine alcohols for any of the above examples of modified anti-aging agents can be substituted to include any material according to the techniques disclosed herein. Additionally, any of the techniques in the above examples can be modified or combined with other examples or techniques described herein. Comparative Example 1
[0106] Tall Oil Pitch: Experiments were performed involving PG64-22 blends containing 5 or 10% unmodified tall oil pitch. The tall oil pitch was obtained from Union Camp under the trade name Tallex. It is no longer commercially available. Sample blends were generated and aged according to ASTM D65217 at 20 and 40 hours PAV.
[0107] Binder 6 contained 95% PG64-22 with 5% tall oil pitch added.
[0108] Binder 7 contained 90% PG64-22 with 10% tall oil pitch added.
[0109] The binder blend was produced by mixing the ingredients in a 1 gallon can low shear LIGHTING mixer at temperatures between 187.8°C and 204°C (370°F and 400°F) for approximately 30 minutes.
[0110] 4mm DSR tests were performed under the aging conditions given below to determine the low temperature S-critical and M-critical grades of the blends under different aging conditions. The ΔTc, obtained by subtracting the low temperature M-critical value from the low temperature S-critical value, was determined for each aging condition. [Table 6]
[0111] The data in Table 5 show that unmodified tall oil pitch in binders 6 and 7 failed to improve (e.g., provide a more positive ΔTc) the 40 hour PAV aged samples compared to PG64-22 without additive.
[0112] Thus, although the preferred embodiments of the disclosed compounds, compositions, and methods have been described, those skilled in the art will readily understand that the teachings found herein may be applied to still other embodiments of the appended claims. The complete disclosures of all patents, patent applications, publications, and electronically available materials cited herein are incorporated by reference. The foregoing detailed description and examples are given for clarity of understanding only. No unnecessary limitations are to be understood therefrom. The present invention is not limited to the exact details shown and described, because variations obvious to those skilled in the art are included within the scope of the invention as defined by the claims. The invention disclosed herein by way of example may, in some embodiments, be suitably practiced in the absence of any element not specifically disclosed herein.
Claims
1. An asphalt-based roofing material, adhesive or sealant, an asphalt binder comprising at least one of virgin asphalt binder, airblown virgin asphalt binder, recycled asphalt binder material (RAP) including asphalt paving materials, or recycled asphalt binder material (RAS) including asphalt shingles; and an anti-aging agent that is the reaction product of a component comprising: (i) a first material comprising a compound containing one or more carbonyl groups; and (ii) a second material that reacts with the one or more carbonyl groups of the first material to add hydroxyl groups to the reaction product, wherein the anti-aging agent comprises a hydroxyl number of greater than 25 mg KOH / g; An asphalt binder composition comprising:
1. An asphalt-containing material comprising:
2. The asphalt-containing material of claim 1, wherein the asphalt-containing material is a roofing material and the asphalt binder composition is a hot-applied asphalt membrane that provides a moisture barrier.
3. 10. The asphalt-containing material of claim 1, wherein the asphalt-containing material is a roofing material including a moisture barrier, a waterproof film, or an underlayment.
4. 2. The asphalt-containing material of claim 1, wherein the asphalt-containing material is a roofing material comprising a roofing substrate coated or saturated with the asphalt binder composition.
5. A method for forming an asphalt-containing material, including an asphalt-based roofing material, adhesive or sealant, wherein the asphalt-containing material is a reaction product of an asphalt binder comprising at least one of virgin asphalt binder, air-blown virgin asphalt binder, recycled asphalt binder material (RAP) from recycled asphalt pavement material, or recycled asphalt binder material (RAS) from recycled asphalt shingles, and components including (i) a first material comprising a compound containing one or more carbonyl groups, and (ii) a second material that reacts with the one or more carbonyl groups of the first material to add hydroxyl groups to the reaction product, wherein the second material comprises an anti-aging agent having a hydroxyl number of greater than 25 mg KOH / g.
1. A method for retarding the effects of aging of an asphalt-containing material, comprising:
6. 5. The asphalt-containing material of claim 4, wherein the roofing substrate comprises a fibrous mat, and the roofing material further comprises roofing aggregate applied to at least one surface of the roofing material.
7. 7. The asphalt-containing material of any one of claims 1 to 4 and 6, wherein the one or more carbonyl groups of the first material comprise one or more carboxylic acid groups, anhydride groups, ester groups, amide groups, or imide groups.
8. 8. The asphalt-containing material of any one of claims 1 to 4, 6 and 7, wherein the first material comprises one or more of a plant-based material, a rosin acid, or a fatty acid.
9. 9. The asphalt-containing material of any one of claims 1 to 4 and 6 to 8, wherein the first material comprises one or more of castor oil, cashew nut shell oil, cottonseed oil, corn oil, peanut oil, rapeseed oil, rice bran oil, safflower oil, sarsaparilla root oil, soybean oil, sunflower oil, tall oil, vegetable oil, and wheat germ oil.
10. The first material is C 1 ~C 36 10. The asphalt-containing material of any one of claims 1 to 4 and 6 to 9, comprising at least one of a carboxylic acid, a dicarboxylic acid, an anhydride, a keto acid, a compound containing both a carboxylic acid group and an anhydride group, or a tricarboxylic acid.
11. 11. The asphalt-containing material of any one of claims 1 to 4 and 6 to 10, wherein the first material comprises at least one of tall oil, unrefined tall oil, or tall oil pitch.
12. 12. The asphalt-containing material of any one of claims 1 to 4 and 6 to 11, wherein the first material comprises a coal-based material or a petroleum-based material.
13. 13. The asphalt-containing material of any one of claims 1 to 4 and 6 to 12, wherein the anti-aging agent is a reaction product of components further comprising iii) a third material having an unsaturated group that reacts with at least one of the first material or the second material in forming the reaction product, the third material comprising at least one of DCPD, piperylene, isoprene, or an unsaturated alcohol.
14. 14. The asphalt-containing material of any one of claims 1 to 4 and 6 to 13, wherein the second material comprises a polyol, an amine alcohol, or a combination thereof.
15. 15. The asphalt-containing material of any one of claims 1-4 and 6-14, wherein the second material comprises one or more of ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, dimethylolpropionic acid, glycerin, trimethylolpropane, neopentyl glycol, pentaerythritol, dipentaerythritol, sorbitol, sucrose, polyethylene glycol, polypropylene glycol, methanolamine, dimethylethanolamine, ethanolamine, aminomethylpropanol, polysulfide polyols, or propanolamine.
16. 16. The asphalt-containing material of any one of claims 1 to 4 and 6 to 15, wherein the anti-aging agent has a hydroxyl number of greater than 35 mg KOH / g.
17. 16. The asphalt-containing material of any one of claims 1 to 4 and 6 to 15, wherein the anti-aging agent has a hydroxyl number of greater than 50 mg KOH / g.
18. 18. The asphalt-containing material of any one of claims 1 to 4 and 6 to 17, wherein the anti-aging agent has an acid number of less than 100.
19. 19. The asphalt-containing material of any one of claims 1 to 4 and 6 to 18, wherein the asphalt binder mixed with the anti-aging agent provides a ΔTc of greater than or equal to -5.0°C after 40 hours PAV aging at 100°C.
20. 20. The asphalt-containing material of any one of claims 1 to 4 and 6 to 19, wherein the asphalt binder composition comprises 0.5 weight percent (wt%) to 15 wt% of the anti-aging agent relative to the asphalt binder.
21. The method of claim 5, further comprising the step of coating or saturating a roofing substrate with the asphalt binder to produce a roofing material, the roofing substrate comprising a fibrous mat, and the roofing material further comprising roofing aggregate applied to at least one surface of the roofing material.
22. 22. The method of claim 5 or 21, wherein the one or more carbonyl groups of the first material comprise one or more carboxylic acid groups, anhydride groups, ester groups, amide groups, or imide groups.
23. 23. The method of any one of claims 5, 21 and 22, wherein the first material comprises one or more of a plant-based material, a rosin acid, or a fatty acid.
24. 24. The method of any one of claims 5 and 21-23, wherein the first material comprises one or more of castor oil, cashew nut shell oil, cottonseed oil, corn oil, peanut oil, rapeseed oil, rice bran oil, safflower oil, sarsaparilla root oil, soybean oil, sunflower oil, tall oil, vegetable oil, wheat germ oil, tall oil, unrefined tall oil, or tall oil pitch.
25. 25. The method of any one of claims 5 and 21-24, wherein the second material comprises a polyol, an amine alcohol, or a combination thereof.
26. 26. The method of any one of claims 5 and 21-25, wherein the anti-aging agent has a hydroxyl number of greater than 50 mg KOH / g.